Diversity of Crustaceans Bycatch of Blue Swimming Crab (Portunus pelagicus) Fisheries of Landed in Leppe village, Soropia District, Konawe Regency: Keragaman Krustasea Bycatch Perikanan Rajungan (Portunus pelagicus) yang Didaratkan di Desa Leppe, Kecamatan Soropia, Kabupaten Konawe - Andika Resa Pratama; Abdul Hamid; Syamsul Kamri; Rahmad Sofyan Patadjai (Journal of Tropical Fisheries Management, 2022)
This research was aiming of find out the diversity of crustaceans bycatch of blue swimming crab (Portunus pelagicus) fisheries of moon period based. The method used was a survey method and sampling of crustacean bycatch was carried out during the period of bright moon (11-15 moon nights) and dark moon (27-1 moon nights). The results showed that there were 20 species of crustacean bycatch found during the study in which 17 species were found during the bright moon and 16 species were found during the dark moon. Thalamita danae species had the highest abundance during the dark and the bright moon period. The number of the male crustaceans bycatch was higher than the females for both bright and dark moon periods.Diversity index crustacean bycatch in both periods (brigh tand dark) ranged from 0.83 to 0.85. The evennes index and dominance index inthe bright and dark moon are the same (0.69 and 0.22, respectively).